Non-commercial Plants of Medicinal Purposes from the Brazilian Biomes for the Treatment of Gastrointestinal Diseases - Pellizzon, Claudia Helena [UNESP]; Rozza, Ariane Leite [UNESP]; Paula Vasconcelos, Paulo Cesar de [UNESP]; Andreo, Marcio Adriano; Vilegas, Wagner [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Govil, JN; Singh, VK (Studium Press Llc, 2010)
Medicinal plants are used, in many cases, with little or without knowledge regarding their pharmacological and toxicological properties. Researches involving natural products are normally guided by the ethnopharmacological knowledge and have been contributing for the drug improvement leading to the determination of new structures and action mechanisms. In this chapter, we will discuss three medicinal plants from Cerrado - Alchornea glandulosa Poepp. & Endl. (Euphorbiaceae), Byrsonima fagifolia Nied. (Malpighiaceae) and Mouriri pusa Gardn.(Melastomataceae) indicating by ethnopharmacological tools to gastrointestinal disturbs. Based on pre-clinical assays (cicatrisation and cytoprotective process in gastric models) that simulated the gastrointestinal pathogenesis in man these plants proved that chemical and pharmacological research can be of an effective therapies safe and efficient against gastroduodenal diseases.
Keywords: Alchornea glandulosa; Byrsonima fagifolia; Mouriri pusa; Gastric ulcer cicatrisation; Colitis